A Survey on Fecal Coliform Count and Total coliform count using filter drinking water samples collected from tea-stalls and roadside restaurants of Mohakhali, Dhaka - Mou, Ummay Moriom (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2019.